Деякі особливості розвитку середньої освіти на cумських землях у другій половині ХIХ – на початку ХХ ст. - Демиденко, Н.М. (Сіверщина в історії України, 2020)
У статті висвітлено діяльність перших навчальних закладів
на сумських землях – повітових чоловічих та жіночих училищ, –
які надавали початкову та середню освіту.
Відзначена велика роль окремих благодійників і благодійних
товариств, які долучались до фінансування навчальних закладів
та окремих учнів із бідних родин Сумського повіту Харківської губернії. Констатована участь дворян Сумського повіту М.Д. Кондратьєва, І.Г. Харитоненка, В.О. Савича, І.С. Федоровського, І.Т. Лисенка та ін. у підтримці навчання дітей із малозабезпечених родин.
Проаналізовані зусилля сільських громад (на прикладі Путивльського повіту) щодо фінансової підтримки оплати роботи вчителів на початку ХХ ст. У статті використовуються різноманітні епістолярно-мемуарні джерела (спогади Миколи Василенка про
роки навчання в Глухівській прогімназії, уривки із шкільних творів за 1916 рік тощо). The article covers the activities of the first schools in Sumy region, which
provided primary and secondary education: Sunday schools, county men’s
and women’s schools. Attention is drawn to the fact that the progressive
reforms of the 1960s and 1970s, implemented in the Russian Empire, had a
positive effect on changes in the educational process and in the Sumy region.
It is stated that the main purpose of the general educational institutions
of the second half of the 19th - beginning of the 20th centuries was to
provide knowledge that would correspond to the technical development of
the industry at that time. As before, great attention was paid to religious
education, instilling a sense of humanism and love for the country.
The great role of individual philanthropists and charitable societies,
which were involved in financing educational institutions and individual
students from poor families of Sumy county of Kharkiv province, was
noted. Participation of nobles of Sumy county such as M.D. Kondratiiev,
I.H. Kharitonenko, V.O. Savych, I.S. Fedorovskyi, I.T. Lysenko et al. in
charity work was stated. The features of the orphanages for orphan girls
founded by Nataliia Kharytonenko and Mariia Sukhanova are highlighted.
The issue of the founding of the city of Sumy in 1860 by the philanthropists
of the first public library, the funds of which teachers were entitled to free
use, was raised. The library, including until 1915, received foreign periodicals
from Austria-Hungary, Germany and France, as well as all periodicals
published in the Russian Empire. Some philanthropists received the title
of honorary citizen of Sumy for the financial support of the public library.
The great efforts of rural communities (on the example of Putivl County)
to provide financial support for teachers’ salaries at the beginning of the
21st century were analyzed.
Various epistolary-memoir sources (memoirs of Mykola Vasylenko – a
scientist, minister of education and arts of the Hetmanate period (1918)
about the years of study at Hlukhiv secondary school; excerpts from student
works for 1916, etc.) were used in the preparation of the article.
While writing the work general-historical (comparative-historical,
retrospective) methods were used. The source analysis method was
also actively used.